Is Endothelial Neoplastic Implantation the Reason for the Intravenous Leiomyomatosis in the Heart without Direct Growth from Vena Cava? A Report of Six Cases - Li, Yunzhu; Miao, Qi; Cheng, Ninghai; Liu, He; Ma, Guotao (The Thoracic and Cardiovascular Surgeon, 2019)
Intravenous leiomyomatosis (IVL) with intracardiac involvement is a rare condition. Previous case reports have described direct tumor extension into the vena cava and cardiac chamber. Six patients with intracardiac lesion without direct growth from the IVC were admitted. Surgical resections were performed including total hysterectomy and bilateral salpingo-oophorectomy. Post-operative pathology revealed intravenous leiomyomatosis. The endothelial neoplastic implantation of IVL is a possible reason for the disseminated lesions of IVL within venous system. Awareness of this entity helps clinicians avoid misdiagnosis and take appropriate treatment.
Keywords: intravenous leiomyomatosis; cardiac involvement; metastasis; endothelial neoplastic implantation